An Analysis of Camera Translator Application’s Results in Perspective of Nababan’s Theory - Rizki Adha; Muhammad Dalimunthe; Sholihatul Hamidah Daulay (Sintaksis : Publikasi Para ahli Bahasa dan Sastra Inggris, 2024)
This research aims to analyze the quality of the Camera Translator application based on the perspective of Nababan’s theory. The reason for conducting this research is because of the importance of understanding the quality of the camera translator application which is increasingly used in everyday life and education, especially to overcome limited foreign language skills. The method used in this research is descriptive qualitative. The research instruments used include the Camera translator application and translation quality assessments based on Nababan theory indicators, namely accuracy, readability, and acceptability. The data source in this research is written text, a part of a short story entitled “April in Moscow” translated using a camera translator application. The research data is in the form of text translation results from English to Indonesian taken by taking pictures of the text to be translated. The research results show that camera translator applications have varying accuracy, readability, and acceptability levels. From data sources totaling 63 sentences from part of the short story "April in Moscow", 41 sentences were translated accurately, 15 sentences were translated less accurately, and 7 sentences were not accurate. In terms of acceptability, 39 sentences were acceptable, 14 sentences were less acceptable, and 10 sentences were not acceptable. From the readability aspect, 44 sentences are readable, 12 sentences are less readable, and 7 sentences are not readable. In general, the translation results are quite good, however, there are several errors in the translation of certain words and phrases which affect the overall quality of the translation. This research concludes that the camera translator application has good quality in transferring the meaning of written text from English to Bahasa. It also can be a useful tool for translating texts in daily life and education, but users must remain careful about potential translation errors. Evaluation of translation quality using Nababan's theory can provide deeper insight into the advantages and disadvantages of camera translator applications.